Comparison of splinting and splinting plus low-level laser therapy in idiopathic carpal tunnel syndrome - YAĞCI, İLKER; GÜNDÜZ, OSMAN HAKAN (SPRINGER LONDON LTD, 2009)
This study aimed to compare the short-term efficacy of splinting (S) and splinting plus low-level laser therapy (SLLLT) in mild or moderate idiopathic carpal tunnel syndrome (CTS) with a prospective, randomized controlled study. The patients with unilateral, mild, or moderate idiopathic CTS who experienced symptoms over 3 months were included in the study. The SLLLT group received ten sessions of laser therapy and splinting while S group was given only splints. The patients were evaluated at the baseline and after 3 months of the treatment. Follow-up parameters were nerve conduction study (NCS), Boston Questionnaire (BQ), grip strength, and clinical response criteria. Forty-five patients with CTS completed the study. Twenty-four patients were in S and 21 patients were in SLLLT group. In the third-month control, SLLLT group had significant improvements on both clinical and NCS parameters (median motor nerve distal latency, median sensory nerve conduction velocities, BQ symptom severity scale, and BQ functional capacity scale) while S group had only symptomatic healing (BQ symptom severity scale). The grip strength of splinting group was decreased significantly. According to clinical response criteria, in SLLLT group, five (23.8%) patients had full and 12 (57.1%) had partial recovery; four (19%) patients had no change or worsened. In S group, one patient (4.2%) had full and 17 (70.8%) partial recovery; six (25%) patients had no change or worsened. Additionally, applied laser therapy provided better outcomes on NCS but not in clinical parameters in patients with CTS.
Keywords: Idiopathic carpal tunnel syndrome; Laser therapy; Splinting; RANDOMIZED CONTROLLED-TRIAL; LOCAL STEROID INJECTION; ADMINISTERED BOSTON QUESTIONNAIRE; ELECTROPHYSIOLOGICAL FINDINGS; ULTRASOUND; OUTCOMES; NEUROLYSIS; SEVERITY; RELEASE; HAND